1992
DOI: 10.1088/0034-4885/55/5/001
|View full text |Cite
|
Sign up to set email alerts
|

ULF waves-their relationship to the structure of the Earth's magnetosphere

Abstract: The Earth's magnetosphere is highly structured, in terms of both magnetic field and plasma characteristics. This structure has a profound influence on the propagation of plasma waves, especially ultra-low-frequency (ULF) waves With mHz frequencies, which have wavelengths comparable with typical magnetospheric dimensions. In thk review we illustrate bow the basic theory of ULF hydromagnetic wave propagation in an infinite, homogeneous, uniformly magnetized plasma has been extensively modified to cope with the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 246 publications
4
61
0
1
Order By: Relevance
“…The occurrence of such a low frequency under quiet conditions agrees well with a statistical study performed by Cummings et al (1969). It is di cult to decide on the basis of our data which mode has been observed exactly, because the eigenfrequencies depend on the density distribution along the ®eld lines and in the equatorial plane (Cummings et al, 1969) and are very di erent under night-time and day-time conditions (Allan and Poulter, 1992).…”
Section: Theoretical Considerationssupporting
confidence: 87%
“…The occurrence of such a low frequency under quiet conditions agrees well with a statistical study performed by Cummings et al (1969). It is di cult to decide on the basis of our data which mode has been observed exactly, because the eigenfrequencies depend on the density distribution along the ®eld lines and in the equatorial plane (Cummings et al, 1969) and are very di erent under night-time and day-time conditions (Allan and Poulter, 1992).…”
Section: Theoretical Considerationssupporting
confidence: 87%
“…Solar wind dynamic pressure pulses that compress the magnetopause and launch fast mode waves can stimulate FLRs in the dayside magnetosphere around magnetic local noon . Numerical studies of ULF waves excited by solar wind impulses have confirmed coupling between global cavity modes and FLRs (Allan and Poulter 1992;Zhu et al 1991;Lee et al 1989;Zhang et al 2009). …”
Section: Introductionmentioning
confidence: 91%
“…Surface waves generated by the K-H instability propagate earthward to excite field line resonances (FLRs) Claudepierre et al 2008). In contrast, when a solar wind dynamic pressure Allan and Poulter (1992)) pulse impinges on the magnetopause, it produces fast mode waves that propagate into the inner magnetosphere, transferring energy from the solar wind in the process. The generation mechanisms for ULF waves depend on the local time region in which they operate.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that ULF waves in the Pc 3 (10-100 mHz) band, observed at low and middle latitudes, are a consequence of field line resonance (FLR) stimulated by fast mode oscillations in the plasmasphere and magnetosphere [Kivelson and Southwood, 1986;Allan et al, 1986;Allan and Poulter, 1992]. In this situation the signature observed on the ground is that of the FLR and the frequency increases with decreasing latitude.…”
Section: Introductionmentioning
confidence: 99%